A Study of How Disney Animated and Non-Animated Movie on Students’ Vocabulary Mastery: Insights From Students' Perception - Ritonga, Gustina Permatasari; Benni Ichsanda Rahman Hz (Universitas Cokroaminoto Palopo, 2024)
Vocabulary is an important thing for every student in learning English. To improve vocabulary mastery, there are several media that can be used, one of which is animated and non-animated Disney movies. This study aims to explore in-depth information on how students’ perception on the use of Disney's animated and non-animated movies in the context of improving their vocabulary mastery. To collect the data researcher involved two main methods used a modified questionnaire and semi-structured interviews with qualitative approach. The data was analyzed through two different ways using content analysis to analyze the questionnaire and qualitative interpretation from interviews with the participants. The results of this study revealed that both types of Disney movies have a positive impact on improving students' vocabulary acquisition. Furthermore, this study provides a foundation for the development of more inclusive teaching strategies.